Fluorescent nanoparticles with ultralow chromophore loading for long-term tumor-targeted imaging. (15th July 2020) - Su, Ya; Lv, Chunyan; Zhang, Yujian; Liu, Shi; Xie, Zhigang; Zheng, Min
Abstract: Recently, organic dyes with aggregation-induced emission (AIE) have attracted much attention in bioimaging and diagnostics. Relatively, the application of traditional dyes has diminished because of aggregation-caused quenching (ACQ). In this work, we compare the imaging ability of nanoparticle formulations of these two kinds of dyes. Boron dipyrromethene (BODIPY) was chosen as a representative of the ACQ dyes, and an aggregation-induced emission (AIE) dye BPMT was used for comparison. BODIPY and BPMT were entrapped into PEG5k -PLA10k to form BODIPY-loaded NPs (BNPs) and BPMT-loaded NPs (ANPs), respectively. In vivo and ex vivo imaging demonstrated that BNP1 with ultralow BODIPY load (0.07%) can effectively accumulate in tumor tissues and enable long-term noninvasive imaging. In contrast, ANP4 with high BPMT load (1.6%) has poor bioimaging ability. In general, our work has certain reference significance for the application of ACQ dyes and AIEgens in bioimaging, diagnostics, and theranostics. Statement of Significance: In this work, Boron dipyrromethene (BODIPY) was chosen as a representative of ACQ dyes. As a control, (Z)-2-(4′-(9H-carbazol-9-yl)-[1, 1′-biphenyl]-4-yl)-3-(7-(4-(bis(4methoxyphenyl)amino) phenyl) benzo[c] [1, 2, 5 ] thiadiazol-4-yl) acrylonitrile (BPMT) was selected as an aggregation-induced emission (AIE) dye. BODIPY and BPMT was entrapped into PEG5k-PLA10k to form BODIPY-loaded NPs (BNPs) and BPMT-loaded NPs (ANPs), respectively. In vivo and ex vivo imaging demonstrated that BNP1 with ultralow BODIPY load (0.07%) can effectively accumulate in tumor tissues and realize long-term noninvasive imaging. The weaknesses of ACQ effect can be converted into advantages by skillful use of nanotechnology, which can not only save the cost but also realize high efficiency targeted cancer imaging. Graphical abstract: Image, graphical abstract